Improving a method for determining the coordinates of a reconnaissance unmanned aerial vehicle by a small-based network of two software-defined radio receivers - Ruban, Igor; Khudov, Hennadii; Biernik, Yelyzaveta; Makoveichuk, Oleksandr; Maliuha, Volodymyr; Yarovyi, Serhii; Khudov, Rostyslav; Khudov, Vladyslav; Poberezhnyi, Leonid; Goncharenko, Olena (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates the process for determining the coordinates of a reconnaissance unmanned aerial vehicle. The task addressed relates to determining the coordinates of a reconnaissance unmanned aerial vehicle using a small-scale network of mobile passive location devices. A method for determining the coordinates of a reconnaissance unmanned aerial vehicle has been improved, which, unlike known ones, involves: – determining bearings for a reconnaissance unmanned aerial vehicle; – using the triangulation method. The accuracy of determining the coordinates of a reconnaissance unmanned aerial vehicle by a small-scale network of two Software-Defined Radio receivers has been assessed. It has been established that the shape and orientation of the error ellipses depends on the position of the reconnaissance unmanned aerial vehicle relative to the Software-Defined Radio receivers. The accuracy of determining the coordinates significantly deteriorates in cases where the polar angle of observation from the center of the base approaches 0° or 180°. The highest accuracy of determining coordinates is achieved when the reconnaissance unmanned aerial vehicle is located on the traverse to the middle of the base. It has been established that for small bases there is a more pronounced unevenness of the dependence of accuracy on the position of the reconnaissance unmanned aerial vehicle compared to larger bases. At long ranges, errors for small bases increase sharply. It has been established that with a decrease in the base length, the area of the error ellipses increases, which indicates a deterioration in the potential accuracy characteristics of the system and an increase in the average circular error. At the same time, the geometric features are preserved, the orientation of the ellipses and the nature of their location relative to the base line remain constant